Simulating future climate changes under the shared socioeconomic pathway scenarios: a case of the black volta basin of Ghana - Kabo-Bah, Amos T.; Siabi, Sarah Elikplim; Siabi, Ebenezer K.; Ahiada, Wisdom Bruce; Cobbina, Nana Asirifi (Frontiers in Environmental Science, 2025)
This study assessed the potential impacts of climate change on Ghana’s Black Volta Basin (BVB) to inform the development of robust adaptation strategies for the region’s vulnerable sectors. Projections from 14 Global Climate Models (GCMs) under four CMIP6 scenarios (SSP1‐2.6, SSP2‐4.5, SSP3‐7.0, and SSP5‐8.5) were analyzed. The predictive skill of an ensemble of bias‐corrected data was rigorously evaluated against individual bias‐corrected and raw GCM outputs, with the coefficient of determination (R2) serving as a primary performance metric. The ensemble bias‐corrected data demonstrated superior performance, particularly for precipitation, where the R2 value increased markedly from values as low as 0.001 in the raw data to a range of 0.87‐0.99. Projections indicate a consistent trend of substantial warming and an overall decline in precipitation by 2050 across all scenarios, with rainfall reductions anticipated in most months except August and September. The most significant temperature increases, ranging from 1.0 °C to 7.5 °C for monthly averages, were projected under the SSP2‐4.5, SSP3‐7.0, and SSP5‐8.5 scenarios. Spatial analysis revealed pronounced warming in the northern part of the basin, where annual rainfall under SSP5‐8.5 could decline to 800‐900 mm from historical norms of 1,000‐1,400. The projected climatic changes pose significant threats to livelihoods, water resources, agricultural productivity, and energy security. The hydroelectric sector, a critical component of the national grid supported by the Bui and Akosombo dams, is likely to face challenges from reduced water inflows, increasing the risk of power outages. These findings underscore the critical necessity for proactive adaptation. Key recommendations include the promotion of drought‐resistant crops, implementation of advanced water management strategies, revision of energy policies, and investment in climate‐resilient infrastructure to enhance the long‐term sustainability of the BVB.